Sistema fotovoltaico para iluminação e alimentação de pequenos equipamentos em corrente contínua - Silva, Felinto Sérgio Firmeza e (2010)
This work presents the development of a photovoltaic system (PV) to supply electricity in DC voltage to household appliances in rural areas. The system consists of photovoltaic panel, battery bank, battery charger and a boost converter. The system was designed to support two days of autonomy, even under conditions of minimal solar radiation. The solar energy is captured by PV panels and stored in a lead acid batterie bank. The battery charger enables the charge of the batteries on maximum power point (MPP) of the PV panel. The chosen topology for the charger was a boost interleaved, which operation can be compared with two classic boost converters working in parallel, with 180° phase shift between the controls of the switches. The load is supplied through a high gain boost converter. The complete design of the system and its control are presented. Finally, the simulation results and the main experimental results obtained from a laboratory prototype and from a prototype in operation in rural school are shown.